PENGARUH PENAMBAHAN BEBERAPA LEVEL GLUTATHIONE DALAM PENGENCER AIR KELAPA KUNING TELUR TERHADAP KUALITAS SEMEN SAPI ANGUS (The effects of adding some levels of glutathione in egg yolk coconut water on the quality of angus bull semen) - Desiderius S. Agung; Aloysius Marawali; Kirenius Uly; Franky M.S. Telupere (JURNAL NUKLEUS PETERNAKAN, 2023)
The purpose of this study was to determine the effect of adding several levels of glutathione in egg yolk coconut water dilution (EY-CW) on the quality of angus bull semen during storage. The material used is fresh semen from one 3 years old angus bull that has good quality. Good quality semen was dilut with EY-CW diluent with the addition of glutathione at the levels of 0% (T0), 0.1% (T1), 0.2% (T2), and 0.3% (T3). After dilution, the semen stored at 3-5oC. Evaluation of semen after dilution was carried out every 24 hours of storage for motility, viability, abnormalities and survival of spermatozoa. The research data were analyzed with analysis of variance and continued with the Duncan test. The results showed that the addition of 0.2% glutathione level (T2) had the best quality (P<0.05) compared to other treatments, namely motility (47.00±2.09%), viability (57.64±3.08%), abnormality (6.20±1.29%) and survival (4.00±0.00 days). It was concluded that the addition of a glutathione level of 0.2% in the AK-KT diluent provided the best and more effective influence in maintaining the quality of angus bull liquid semen until the fourth day of storage.